2004
DOI: 10.1029/2003rg000142
|View full text |Cite
|
Sign up to set email alerts
|

A review of applications to constrain pumping test responses to improve on geological description and uncertainty

Abstract: [1] This review examines the single-phase flow of fluids to wells in heterogeneous porous media and explores procedures to evaluate pumping test or pressure-response curves. This paper examines how these curves may be used to improve descriptions of reservoir properties obtained from geology, geophysics, core analysis, outcrop measurements, and rock physics. We begin our discussion with a summary of the classical attempts to handle the issue of heterogeneity in well test analysis. We then review more recent ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 137 publications
(236 reference statements)
2
30
1
1
Order By: Relevance
“…Pavelic et al (2006) found core values to be 50 times lower than field permeabilities, which they concluded to be due to the small observation scale and the fact that well-cemented cores can be sampled more easily. Raghavan (2004) claimed that pressure tests always yield larger permeabilities than cores, but that the apparent transmissivity of single well tests always decreases with the radius of influence. On the other hand, for fine to coarse sandstones, Runkel et al (2006) did not observe a systematic deviation between a large number of permeabilities determined by hydraulic tests and core observations.…”
Section: Permeability Discrepancy With Respect To Core Valuesmentioning
confidence: 99%
“…Pavelic et al (2006) found core values to be 50 times lower than field permeabilities, which they concluded to be due to the small observation scale and the fact that well-cemented cores can be sampled more easily. Raghavan (2004) claimed that pressure tests always yield larger permeabilities than cores, but that the apparent transmissivity of single well tests always decreases with the radius of influence. On the other hand, for fine to coarse sandstones, Runkel et al (2006) did not observe a systematic deviation between a large number of permeabilities determined by hydraulic tests and core observations.…”
Section: Permeability Discrepancy With Respect To Core Valuesmentioning
confidence: 99%
“…was incorporated. Our attempts are summarized in Raghavan et al (2001Raghavan et al ( , 2004, Thomas et al (2005) and Raghavan (2004).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, our goal is to examine the characteristics of test responses in such situations and understand the challenges one may face when complex geology is encountered. Conceptually we have found it difficult to apply purely stochastic formulations without reference to the geologic imprint (Raghavan et al, 2001;Raghavan, 2004). In the present context, the term complex geology refers to a geological body that is markedly heterogeneous and anisotropic with multiscale features including features that may cause local barriers to flow and give rise to distorted flow paths.…”
Section: Introductionmentioning
confidence: 98%
“…Significant deviations from standard solutions have been observed in pumping tests (Raghavan, 2004). Moreover, it has been reported that 1/ f dynamics are observed in time series of pumping test (Zhongwei & You-Kuan, 2007) and we showed evidence that support their findings.…”
Section: Discussionmentioning
confidence: 99%